Poverty and Iinequality Sstudies in Iran A Book Rreview of “The Necessity of Fighting the Poverty and Inequality in Iran” - Mohamad Farhadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Poverty and inequality in Iran are two important phenomena the depth and breadth of which have attracted the attention of social and economic thinkers and have been studied from various perspectives. "The Necessity of Fighting Poverty and Inequality in Iran" by Saeed Madani Qahfarhchi is one of these research findings.Reviewing and criticizing these studies are a necessary prerequisite for defining literature on poverty and inequality in Iran. From the methodological point of view, the present paper criticizes this book and provides some theoretical imperatives and a way to complete it. In a critique, this article is not seen as a defect, which provides some suggestions for the completion of this project with an empathetic attitude. After the introduction of the effect of some shortcomings, the chapters of the book are discussed, and in the next step, the systematic analysis of the methodological, theoretical, and epistemological perceptions of the book is introduced.The result of this article is that the approach of the book is more descriptive and does not provide an explanation of poverty in Iran. Accordingly, the book does not introduce the category of inequality and its causes and reasons in Iran. The lack of a deliberate look and a definite stance on poverty and inequality in this book is one of the main points that this article emphasizes.